High-strength alkali-resistant anti-skinning castable and preparation method thereof

Low-aluminum mullite composite phase materials are prepared by mixing low-grade bauxite, coal gangue, and potassium feldspar. Combining the high-temperature characteristics of high-silicon oxide glass phase and metal silicon powder, silicon carbide reactions are generated in situ, solving the problem of loose structure and high cost of existing anti-scaling castables at high temperatures, and achieving efficient anti-scaling and alkali resistance.

CN119638393APending Publication Date: 2025-03-18YANGQUAN JINYU TONGDA HIGH TEMPERATURE MATERIALS +3
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411914937.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The existing anti-crusting castable materials have loose structures at high temperatures and weak thermal shock resistance, making it difficult to maintain the anti-crusting effect of refractory materials throughout the use cycle. At the same time, the widespread application of products is hindered by the reliance on high-cost silicon carbide and magnesium aluminum spinel.

Method used

By mixing the proportions of low-grade bauxite, coal gangue, and potassium feldspar, low-aluminum mullite composite materials are prepared, and the high-temperature liquid phase viscosity of high-silicon oxygen glass phase and the high-temperature melting characteristics of metal silicon powder are used to fill the pores on the surface of the castable, and the silicon carbide series solid phase reaction is generated in situ to improve the anti-scaling ability.

Benefits of technology

It significantly improves the anti-skining properties and alkali resistance of the anti-skining castable material, reduces the expansion coefficient, improves the strength and thermal shock resistance at high temperatures, and is suitable for key parts such as cement kiln tail smoke chambers, decomposition furnaces, and preheaters, while reducing raw material costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119638393A_ABST
    Figure CN119638393A_ABST
Patent Text Reader

Abstract

The invention provides a high-strength alkali-resistant anti-skinning castable which comprises the following components in parts by weight: 60-70 parts of low-aluminum mullite complex-phase raw material particles, 8-12 parts of low-aluminum mullite complex-phase raw material fine powder, 6-8 parts of silica fume, 7 parts of aluminate cement, 4-6 parts of alumina micro powder, 1-2 parts of metal silicon powder, 2-4 parts of crystalline flake graphite, 0.1 part of explosion-proof fiber and 0.1-0.15 part of a water reducing agent. The invention also provides a preparation method of the high-strength alkali-resistant anti-skinning castable. According to the preparation formula and the preparation method disclosed by the invention, the comprehensive utilization rate and the additional value of a large amount of low-order aluminum-silicon resources can be remarkably improved, and the anti-skinning capability of the castable in a service process is improved by in-situ generation of a silicon carbide series solid-phase reaction in a matrix. According to the technical scheme, the high-strength alkali-resistant anti-skinning castable is developed at low cost by using solid waste resources in a high-valued manner on the premise of not additionally adding silicon carbide and magnesium aluminate spinel, so that the product has a wide market prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of refractory materials, and in particular to a high-strength alkali-resistant and anti-scaling castable and a preparation method thereof. Background Art

[0002] With the development of urbanization and economy, the amount of urban garbage and industrial solid waste is increasing year by year. Cement kiln co-treatment technology plays an increasingly important role in the low-carbon transformation and upgrading of cement enterprises and the resource utilization and harmlessness of solid waste. However, in the process of promoting the development of cement kiln co-treatment technology, the content of chlorine, sulfur and alkali enriched by hot air circulation in the dry decomposition system has increased significantly, aggravating the erosion of refractory materials in the smoke chamber, decomposition furnace and preheater in the kiln tail decomposition system, and reacting with the kiln lining, causing clinker powder to adhere to the surface of the kiln lining, forming a crust blockage that is difficult to clean, reducing the effective space in the kiln, and even making it impossible for materials to pass normally. my country has rich aluminum silicon mineral resources, but most of them are of medium and low grade and cannot be effectively utilized. The large amount of bauxite and coal gangue with an aluminum content of less than 60% mined each year can only be landfilled or piled up in the open air, which greatly damages the ecological environment. With the increasing depletion of natural resources, if we can dissolve the cristobalite in the silicon-aluminum refractory clinker into the glass phase through microstructure control technology, eliminate the adverse effects caused by the cristobalite phase change, optimize the ratio of high-silica glass phase to mullite, and prepare a mullite-high-silica glass low-aluminum composite material with a needle-like mullite interwoven network structure, and at the same time utilize the high viscosity of the high-silica glass phase at high temperature to prepare a high-strength, alkali-resistant and anti-scaling castable for cement kilns, it will not only improve the anti-scaling performance of the kiln when it is running at high temperature, but also has important significance for improving the utilization rate and added value of bulk low-grade aluminum silicon resources.

[0003] In order to improve the alkali resistance and anti-skinning performance of the castable, some people in the prior art have tried to introduce silicon carbide and magnesium aluminum spinel into the product system. The Chinese patent with the authorization announcement number CN 115650749 B discloses a high-strength anti-skinning castable, which contains 45-55 parts by weight of silicon carbide particles, 10-13 parts of magnesium aluminum spinel powder, 9-11 parts of aluminum oxide powder, 3-5 parts of calcium aluminate cement, and then add an appropriate amount of water reducer, and mix the above raw materials with water and stir to prepare the product. When using this castable, although in the early stage of use, as the silicon carbide oxidizes to form a silicon oxide protective film, silicon carbide has a non-wetting effect on alkali, etc., and the high-temperature expansion of the aluminum-magnesium spinel powder can fill the pores and prevent further erosion by alkali vapor, this series of reactions can improve the anti-scaling effect, but in the later stage of use, as the silicon carbide oxidation worsens, the loose structure leads to high-temperature strength failure, and the expansion of the magnesium-aluminum spinel causes the castable's thermal shock resistance to weaken, making it difficult to maintain the anti-scaling effect of the refractory material throughout the entire service life. In addition, the current market prices of silicon carbide and magnesium-aluminum spinel remain high, and the high cost hinders the widespread application of this product.

[0004] In view of the low utilization rate of low-grade aluminum silicon resources in my country, the present invention prepares low-aluminum mullite composite materials with the help of phase control technology, and on this basis provides a high-strength alkali-resistant anti-scaling castable and a preparation method thereof, and attempts to improve the anti-scaling performance of the anti-scaling castable. Summary of the invention

[0005] The present invention attempts to provide a high-strength alkali-resistant anti-scaling castable and a preparation method thereof, which improves the anti-scaling performance of the anti-scaling castable while making full use of a large amount of low-grade aluminum silicon resources in my country.

[0006] The first aspect of the present invention provides a high-strength alkali-resistant and anti-scaling castable, characterized in that, in terms of weight parts, it comprises 60 to 70 parts of low-aluminum mullite complex phase raw material particles, 8 to 12 parts of low-aluminum mullite complex phase raw material fine powder, 6 to 8 parts of silica fume, 7 parts of aluminate cement, 4 to 6 parts of alumina powder, 1 to 2 parts of metallic silicon powder, 2 to 4 parts of flake graphite, 0.1 part of explosion-proof fiber, and 0.1 to 0.15 parts of water reducer; the total weight parts of the low-aluminum mullite complex phase raw material particles, the low-aluminum mullite complex phase raw material fine powder, the silica fume, the aluminate cement, the alumina powder, the metallic silicon powder, and the flake graphite is 100 parts, and the explosion-proof fiber and the water reducer are added additionally.

[0007] The low-aluminum mullite multiphase raw material used in the low-aluminum mullite multiphase raw material particles and the low-aluminum mullite multiphase raw material fine powder is prepared by the following preparation method:

[0008] According to the weight percentage, 10 to 90 parts of grade 4 raw bauxite, 0 to 80 parts of coal gangue, and 10 parts of potassium feldspar are weighed, crushed into particles below 20 mm, loaded into a ball mill, and wet-milled for 10 to 20 hours, until the ball mill mud 325 mesh screening rate is ≥90%, and the mud and water are separated by a plate and frame filter press. After the mud is trapped for 24 hours, it is extruded into a shape using a vacuum extruder, dried at 110 to 130°C for 24 hours, and the dried sample is fired at a high temperature of 1560°C for 3 to 6 hours and then crushed to obtain the product;

[0009] Among them, the aluminum-silicon ratio A / S of the quaternary raw bauxite is 1.0-1.1, the mass fraction of Fe2O3 is ≤2.0%, and the mass fraction of R2O (K2O+Na2O) is ≤0.5%; the aluminum-silicon ratio A / S of the coal gangue is 0.8-0.9, the mass fraction of Fe2O3 is ≤1.5%, and the mass fraction of R2O (K2O+Na2O) is ≤0.5%; the aluminum-silicon ratio A / S of the potassium feldspar is 0.3-0.4, the mass fraction of Fe2O3 is ≤1.0%, and the mass fraction of R2O (K2O+Na2O) is ≥14.0%.

[0010] Preferably, the low-aluminum mullite composite raw material has an aluminum-silicon ratio A / S of 0.8-1.1, a Fe2O3 mass fraction of ≤1.8%, a R2O (K2O+Na2O) mass fraction of ≥2.0%, and a bulk density of 2.2-2.5 g / cm 3 The mullite content is 44-52%, and the high silica glass phase content is 48-56%.

[0011] Preferably, the low aluminum mullite complex phase raw material particles include low aluminum mullite complex phase raw material particles with a particle size of 0 to 8 mm, the low aluminum mullite complex phase raw material fine powder includes low aluminum mullite complex phase fine powder with a particle size of ≤200 mesh, the low aluminum mullite complex phase raw material particles are used as aggregate, the low aluminum mullite complex phase raw material fine powder is used as fine material, and the mass ratio between aggregate and fine material is (60 to 70):(8 to 12).

[0012] Preferably, in the silica ash, the mass percentage of SiO2 is ≥95%, the mass percentage of Fe2O3 is ≤2.0%, and the ignition loss is ≤3.0%.

[0013] Preferably, the aluminate cement is pure calcium aluminate cement, wherein the mass percentage of Al2O3 in the pure calcium aluminate cement is ≥68%, and the 325 mesh screening rate is ≥80%.

[0014] Preferably, the mass percentage of Al2O3 in the alumina micropowder is ≥99%, and the D50 particle size is ≤3μm.

[0015] Preferably, the mass percentage of Si in the metallic silicon powder is ≥98.5%, and the D50 particle size is ≤0.074 mm.

[0016] Preferably, the mass percentage of C in the flake graphite is ≥96.0%, and the D50 particle size is ≤0.074 mm.

[0017] Preferably, the water reducer is a combination of one or more of sodium tripolyphosphate, sodium hexametaphosphate, and naphthalene-based water reducers.

[0018] The second aspect of the present invention provides a method for preparing a high-strength alkali-resistant and anti-scaling castable, characterized in that it comprises the following steps:

[0019] a. First, various raw materials are weighed according to the high-strength alkali-resistant and anti-scaling castable material described in the first aspect;

[0020] b. Put the weighed raw materials into a stirring pot for pre-mixing for 30 seconds, then add water at a uniform speed for stirring for 180 seconds. The amount of water added is 6.5% of the total weight of the raw materials. After stirring evenly, a mixed slurry is obtained;

[0021] c. The obtained mixed slurry is poured into a triple mold for self-flowing molding, and then naturally hardened for 12 hours. After hardening, the slurry is demoulded and placed in a curing box for curing for 24 hours.

[0022] d. Place the cured sample in an oven for drying at a temperature of 110°C for 24 hours;

[0023] e. Place the dried sample into a high-temperature electric furnace for firing at 1100°C or 1400°C for 3 hours. After firing, cool to room temperature and the preparation is complete.

[0024] f. After firing, the anti-scaling performance of the sample shall be tested according to the standard YB-T 4193-2009, and the alkali resistance shall be tested according to the standard GB / T 14983-2008.

[0025] The invention prepares high-performance low-aluminum mullite composite refractory materials by mixing low-grade bauxite, coal gangue and potassium feldspar, and regulating the relative contents of mullite and high-silica glass phase by designing chemical composition, firing temperature and other means, controlling the content fluctuation of harmful impurities and the generation of quartz phase, and improving the mullite conversion rate, thereby significantly improving the comprehensive utilization rate and added value of bulk low-order aluminum silicon resources; the invention uses the characteristics of high high-temperature liquid phase viscosity of high-silica glass phase in low-aluminum mullite composite materials and high-temperature melting of metallic silicon powder to fill the pores on the surface of the castable, and in-situ generates a series of solid-phase reactions of silicon carbide in the matrix to improve the anti-scaling ability of the castable during service; the technical scheme of the invention aims at low-carbon and environmental protection, develops a series of in-situ technologies, and utilizes solid waste resources in a high-value manner without adding silicon carbide and magnesium-aluminum spinel, and develops high-strength alkali-resistant and anti-scaling castables at low cost, and the product has broad market prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 Shown is an electron microscope photograph of the microstructure of the low-aluminum mullite composite material prepared in Example 2.

[0027] Figure 2 Shown is an electron microscope photograph of the microstructure of the low-aluminum mullite composite material prepared in Example 2.

[0028] Figure 3 Shown are photos of the anti-skinning test results of Examples 1 to 5 and Comparative Example 1. DETAILED DESCRIPTION

[0029] In order to provide a further understanding of the purpose, structure, features, and functions of the present invention, the following detailed description is given in conjunction with the embodiments.

[0030] The present invention attempts to provide a high-strength alkali-resistant anti-scaling castable and a preparation method thereof, which improves the anti-scaling performance of the anti-scaling castable while making full use of a large amount of low-grade aluminum silicon resources in my country.

[0031] The first aspect of the present invention provides a high-strength alkali-resistant and anti-scaling castable, characterized in that, in terms of weight parts, it comprises 60 to 70 parts of low-aluminum mullite complex phase raw material particles, 8 to 12 parts of low-aluminum mullite complex phase raw material fine powder, 6 to 8 parts of silica fume, 7 parts of aluminate cement, 4 to 6 parts of alumina powder, 1 to 2 parts of metallic silicon powder, 2 to 4 parts of flake graphite, 0.1 part of explosion-proof fiber, and 0.1 to 0.15 parts of water reducer; the total weight parts of the low-aluminum mullite complex phase raw material particles, the low-aluminum mullite complex phase raw material fine powder, the silica fume, the aluminate cement, the alumina powder, the metallic silicon powder, and the flake graphite is 100 parts, and the explosion-proof fiber and the water reducer are added additionally.

[0032] The low-aluminum mullite multiphase raw material used in the low-aluminum mullite multiphase raw material particles and the low-aluminum mullite multiphase raw material fine powder is prepared by the following preparation method:

[0033] According to the weight percentage, 10 to 90 parts of grade 4 raw bauxite, 0 to 80 parts of coal gangue, and 10 parts of potassium feldspar are weighed, crushed into particles below 20 mm, loaded into a ball mill, and wet-milled for 10 to 20 hours, until the ball mill mud 325 mesh screening rate is ≥90%, and the mud and water are separated by a plate and frame filter press. After the mud is trapped for 24 hours, it is extruded into a shape using a vacuum extruder, dried at 110 to 130°C for 24 hours, and the dried sample is fired at a high temperature of 1560°C for 3 to 6 hours and then crushed to obtain the product;

[0034] Among them, the aluminum-silicon ratio A / S of the quaternary raw bauxite is 1.0-1.1, the mass fraction of Fe2O3 is ≤2.0%, and the mass fraction of R2O (K2O+Na2O) is ≤0.5%; the aluminum-silicon ratio A / S of the coal gangue is 0.8-0.9, the mass fraction of Fe2O3 is ≤1.5%, and the mass fraction of R2O (K2O+Na2O) is ≤0.5%; the aluminum-silicon ratio A / S of the potassium feldspar is 0.3-0.4, the mass fraction of Fe2O3 is ≤1.0%, and the mass fraction of R2O (K2O+Na2O) is ≥14.0%.

[0035] Preferably, the low-aluminum mullite composite raw material has an aluminum-silicon ratio A / S of 0.8-1.1, a Fe2O3 mass fraction of ≤1.8%, a R2O (K2O+Na2O) mass fraction of ≥2.0%, and a bulk density of 2.2-2.5 g / cm 3 The mullite content is 44-52%, and the high silica glass phase content is 48-56%.

[0036] Preferably, the low aluminum mullite complex phase raw material particles include low aluminum mullite complex phase raw material particles with a particle size of 0 to 8 mm, the low aluminum mullite complex phase raw material fine powder includes low aluminum mullite complex phase fine powder with a particle size of ≤200 mesh, the low aluminum mullite complex phase raw material particles are used as aggregate, the low aluminum mullite complex phase raw material fine powder is used as fine material, and the mass ratio between aggregate and fine material is (60 to 70):(8 to 12).

[0037] Preferably, in the silica ash, the mass percentage of SiO2 is ≥95%, the mass percentage of Fe2O3 is ≤2.0%, and the ignition loss is ≤3.0%.

[0038] Preferably, the aluminate cement is pure calcium aluminate cement, wherein the mass percentage of Al2O3 in the pure calcium aluminate cement is ≥68%, and the 325 mesh screening rate is ≥80%.

[0039] Preferably, the mass percentage of Al2O3 in the alumina micropowder is ≥99%, and the D50 particle size is ≤3μm.

[0040] Preferably, the mass percentage of Si in the metallic silicon powder is ≥98.5%, and the D50 particle size is ≤0.074 mm.

[0041] Preferably, the mass percentage of C in the flake graphite is ≥96.0%, and the D50 particle size is ≤0.074 mm.

[0042] Preferably, the water reducer is a combination of one or more of sodium tripolyphosphate, sodium hexametaphosphate, and naphthalene-based water reducers.

[0043] The second aspect of the present invention provides a method for preparing a high-strength alkali-resistant and anti-scaling castable, characterized in that it comprises the following steps:

[0044] a. First, weigh various raw materials according to the aforementioned high-strength alkali-resistant and anti-scaling castable;

[0045] b. Put the weighed raw materials into a stirring pot for pre-mixing for 30 seconds, then add water at a uniform speed for stirring for 180 seconds. The amount of water added is 6.5% of the total weight of the raw materials. After stirring evenly, a mixed slurry is obtained;

[0046] c. The obtained mixed slurry is poured into a triple mold for self-flowing molding, and then naturally hardened for 12 hours. After hardening, the slurry is demoulded and placed in a curing box for curing for 24 hours.

[0047] d. Place the cured sample in an oven for drying at a temperature of 110°C for 24 hours;

[0048] e. Place the dried sample into a high-temperature electric furnace for firing at 1100°C or 1400°C for 3 hours. After firing, cool to room temperature and the preparation is complete.

[0049] f. After firing, the anti-scaling performance of the sample shall be tested according to the standard YB-T 4193-2009, and the alkali resistance shall be tested according to the standard GB / T 14983-2008.

[0050] Examples and Comparative Examples

[0051] Example 1

[0052] The high-strength alkali-resistant and anti-scaling castable comprises, by weight, 70 parts of low-aluminum mullite complex phase raw material particles, 8 parts of low-aluminum mullite complex phase raw material fine powder, 6 parts of silica fume, 7 parts of aluminate cement, 4 parts of alumina powder, 2 parts of metallic silicon powder, 3 parts of flake graphite, 0.1 parts of explosion-proof fiber, and 0.10 parts of sodium tripolyphosphate.

[0053] The method for preparing the low-aluminum mullite composite raw material is as follows:

[0054] According to the weight percentage, 10 parts of low-grade fourth-grade raw alumina, 80 parts of coal gangue and 10 parts of potassium feldspar are weighed, crushed into particles below 20 mm, put into a ball mill, add water and wet grind for 10 to 20 hours, until the ball mill mud 325 mesh screening rate is ≥90%, use a plate and frame filter press to separate the mud and water, after the mud is trapped for 24 hours, use a vacuum extruder to extrude and shape, dry at 110 to 130 ° C for 24 hours, sinter the dried sample at 1560 ° C for 3 to 6 hours, and then crush it to obtain the product.

[0055] The prepared low-aluminum mullite composite raw material has an aluminum-silicon ratio A / S of 0.80, a Fe2O3 mass fraction of 0.76%, a R2O (K2O+Na2O) mass fraction of ≥2.0%, and a bulk density of 2.20 g / cm 3 The mullite content is 44.33%, and the high silica glass phase content is 55.67% (the relative contents of mullite phase and high silica glass phase are detected by hydrofluoric acid dissolution method (YB / T 4584-2017)).

[0056] The aluminum-silicon ratio A / S of the quaternary raw bauxite is 1.0-1.1, the mass fraction of Fe2O3 is ≤2.0%, and the mass fraction of R2O (K2O+Na2O) is ≤0.5%; the aluminum-silicon ratio A / S of the coal gangue is 0.8-0.9, the mass fraction of Fe2O3 is ≤1.5%, and the mass fraction of R2O (K2O+Na2O) is ≤0.5%; the aluminum-silicon ratio A / S of the potassium feldspar is 0.3-0.4, the mass fraction of Fe2O3 is ≤1.0%, and the mass fraction of R2O (K2O+Na2O) is ≥14.0%.

[0057] The low aluminum mullite complex phase raw material particles include low aluminum mullite complex phase raw material particles with a particle size of 0 to 8 mm, the low aluminum mullite complex phase raw material fine powder includes low aluminum mullite complex phase fine powder with a particle size of ≤200 mesh, the low aluminum mullite complex phase raw material particles are used as aggregate, the low aluminum mullite complex phase raw material fine powder is used as fine material, and the mass ratio between aggregate and fine material is (60 to 70): (8 to 12).

[0058] The preparation method of high-strength alkali-resistant and anti-scaling castable comprises the following steps:

[0059] a. First, weigh various raw materials according to the aforementioned high-strength alkali-resistant and anti-scaling castable;

[0060] b. Put the weighed raw materials into a stirring pot for pre-mixing for 30 seconds, then add water at a uniform speed for stirring for 180 seconds. The amount of water added is 6.5% of the total weight of the raw materials. After stirring evenly, a mixed slurry is obtained;

[0061] c. The obtained mixed slurry is poured into a triple mold for self-flowing molding, and then naturally hardened for 12 hours. After hardening, the slurry is demoulded and placed in a curing box for curing for 24 hours.

[0062] d. Place the cured sample in an oven for drying at a temperature of 110°C for 24 hours;

[0063] e. Place the dried sample into a high-temperature electric furnace for firing at 1100°C or 1400°C for 3 hours. After firing, cool to room temperature and the preparation is complete.

[0064] f. After firing, the anti-scaling performance of the sample shall be tested according to the standard YB-T 4193-2009, and the alkali resistance shall be tested according to the standard GB / T 14983-2008.

[0065] Example 2

[0066] The high-strength alkali-resistant and anti-scaling castable comprises, by weight, 68 parts of low-aluminum mullite complex phase raw material particles, 12 parts of low-aluminum mullite complex phase raw material fine powder, 6 parts of silica fume, 7 parts of aluminate cement, 4 parts of alumina micropowder, 1 part of metallic silicon powder, 2 parts of flake graphite, 0.1 parts of explosion-proof fiber, and 0.10 parts of sodium tripolyphosphate.

[0067] The method for preparing the low-aluminum mullite composite raw material is as follows:

[0068] According to the weight proportion, 30 parts of low-grade fourth-grade raw alumina, 60 parts of coal gangue and 10 parts of potassium feldspar are weighed, crushed into particles below 20 mm, put into a ball mill, add water and wet grind for 10 to 20 hours, until the ball mill mud 325 mesh screening rate is ≥90%, use a plate and frame filter press to separate the mud and water, after the mud is trapped for 24 hours, use a vacuum extruder to extrude and shape, dry at 110 to 130 ℃ for 24 hours, sinter the dried sample at 1560 ℃ for 3 to 6 hours, and then crush it to obtain the product.

[0069] The prepared low-aluminum mullite composite raw material has an aluminum-silicon ratio A / S of 0.85, a Fe2O3 mass fraction of 0.95%, a R2O (K2O+Na2O) mass fraction of ≥2.0%, and a bulk density of 2.24 g / cm 3 The mullite content is 45.19%, and the high-silica glass phase content is 54.81% (the relative contents of mullite phase and high-silica glass phase are detected by hydrofluoric acid dissolution method (YB / T 4584-2017)).

[0070] The aluminum-silicon ratio A / S of the quaternary raw bauxite is 1.0-1.1, the mass fraction of Fe2O3 is ≤2.0%, and the mass fraction of R2O (K2O+Na2O) is ≤0.5%; the aluminum-silicon ratio A / S of the coal gangue is 0.8-0.9, the mass fraction of Fe2O3 is ≤1.5%, and the mass fraction of R2O (K2O+Na2O) is ≤0.5%; the aluminum-silicon ratio A / S of the potassium feldspar is 0.3-0.4, the mass fraction of Fe2O3 is ≤1.0%, and the mass fraction of R2O (K2O+Na2O) is ≥14.0%.

[0071] The low aluminum mullite complex phase raw material particles include low aluminum mullite complex phase raw material particles with a particle size of 0 to 8 mm, the low aluminum mullite complex phase raw material fine powder includes low aluminum mullite complex phase fine powder with a particle size of ≤200 mesh, the low aluminum mullite complex phase raw material particles are used as aggregate, the low aluminum mullite complex phase raw material fine powder is used as fine material, and the mass ratio between aggregate and fine material is (60 to 70): (8 to 12).

[0072] The preparation method of the high-strength alkali-resistant and anti-scaling castable is specifically as described above.

[0073] Example 3

[0074] The high-strength alkali-resistant and anti-scaling castable comprises, by weight, 66 parts of low-aluminum mullite complex phase raw material particles, 12 parts of low-aluminum mullite complex phase raw material fine powder, 7 parts of silica fume, 7 parts of aluminate cement, 5 parts of alumina powder, 1 part of metallic silicon powder, 2 parts of flake graphite, 0.1 parts of explosion-proof fiber, and 0.10 parts of sodium hexametaphosphate.

[0075] Wherein, the preparation method of the low-aluminum mullite multiphase raw material is as follows:

[0076] According to the weight proportion, 50 parts of low-grade fourth-grade raw bauxite, 40 parts of coal gangue and 10 parts of potassium feldspar were weighed, crushed into particles below 20 mm, put into a ball mill, wet-milled with water for 10 to 20 hours, until the ball-milled mud 325 mesh screening rate was ≥90%, and the mud and water were separated by a plate and frame filter press. After the mud was trapped for 24 hours, it was extruded into shape by a vacuum extruder, dried at 110 to 130°C for 24 hours, and the dried sample was sintered at 1560°C for 3 to 6 hours and then crushed to obtain the product.

[0077] The prepared low-aluminum mullite composite raw material has an aluminum-silicon ratio A / S of 0.92, a Fe2O3 mass fraction of 1.06%, a R2O (K2O+Na2O) mass fraction of ≥2.0%, and a bulk density of 2.31 g / cm 3 The mullite content is 46.51%, and the high silica glass phase content is 53.49% (the relative contents of mullite phase and high silica glass phase are detected by hydrofluoric acid dissolution method (YB / T 4584-2017)).

[0078] The aluminum-silicon ratio A / S of the quaternary raw bauxite is 1.0-1.1, the mass fraction of Fe2O3 is ≤2.0%, and the mass fraction of R2O (K2O+Na2O) is ≤0.5%; the aluminum-silicon ratio A / S of the coal gangue is 0.8-0.9, the mass fraction of Fe2O3 is ≤1.5%, and the mass fraction of R2O (K2O+Na2O) is ≤0.5%; the aluminum-silicon ratio A / S of the potassium feldspar is 0.3-0.4, the mass fraction of Fe2O3 is ≤1.0%, and the mass fraction of R2O (K2O+Na2O) is ≥14.0%.

[0079] The low aluminum mullite complex phase raw material particles include low aluminum mullite complex phase raw material particles with a particle size of 0 to 8 mm, the low aluminum mullite complex phase raw material fine powder includes low aluminum mullite complex phase fine powder with a particle size of ≤200 mesh, the low aluminum mullite complex phase raw material particles are used as aggregate, the low aluminum mullite complex phase raw material fine powder is used as fine material, and the mass ratio between aggregate and fine material is (60 to 70): (8 to 12).

[0080] The preparation method of the high-strength alkali-resistant and anti-scaling castable is specifically as described above.

[0081] Example 4

[0082] The high-strength alkali-resistant and anti-scaling castable comprises, by weight, 63 parts of low-aluminum mullite multiphase raw material particles, 12 parts of low-aluminum mullite multiphase raw material fine powder, 8 parts of silica fume, 7 parts of aluminate cement, 6 parts of alumina micropowder, 2 parts of metallic silicon powder, 2 parts of flake graphite, 0.1 parts of explosion-proof fiber, and 0.15 parts of naphthalene-based water reducer.

[0083] Wherein, the preparation method of the low-aluminum mullite multiphase raw material is as follows:

[0084] According to the weight proportion, 70 parts of low-grade fourth-grade raw alumina, 20 parts of coal gangue and 10 parts of potassium feldspar were weighed, crushed into particles below 20 mm, put into a ball mill, added with water and wet-milled for 10 to 20 hours, until the ball-milled mud 325 mesh screening rate was ≥90%, and the mud and water were separated by a plate and frame filter press. After the mud was trapped for 24 hours, it was extruded into shape by a vacuum extruder, dried at 110 to 130°C for 24 hours, and the dried sample was sintered at 1560°C for 3 to 6 hours and then crushed to obtain the product.

[0085] The prepared low-aluminum mullite composite raw material has an aluminum-silicon ratio A / S of 0.97, a Fe2O3 mass fraction of 1.25%, a R2O (K2O+Na2O) mass fraction of ≥2.0%, and a bulk density of 2.42 g / cm 3 The mullite content is 51.80%, and the high silica glass phase content is 48.20% (the relative contents of mullite phase and high silica glass phase are detected by hydrofluoric acid dissolution method (YB / T 4584-2017)).

[0086] The aluminum-silicon ratio A / S of the quaternary raw bauxite is 1.0-1.1, the mass fraction of Fe2O3 is ≤2.0%, and the mass fraction of R2O (K2O+Na2O) is ≤0.5%; the aluminum-silicon ratio A / S of the coal gangue is 0.8-0.9, the mass fraction of Fe2O3 is ≤1.5%, and the mass fraction of R2O (K2O+Na2O) is ≤0.5%; the aluminum-silicon ratio A / S of the potassium feldspar is 0.3-0.4, the mass fraction of Fe2O3 is ≤1.0%, and the mass fraction of R2O (K2O+Na2O) is ≥14.0%.

[0087] The low aluminum mullite complex phase raw material particles include low aluminum mullite complex phase raw material particles with a particle size of 0 to 8 mm, the low aluminum mullite complex phase raw material fine powder includes low aluminum mullite complex phase fine powder with a particle size of ≤200 mesh, the low aluminum mullite complex phase raw material particles are used as aggregate, the low aluminum mullite complex phase raw material fine powder is used as fine material, and the mass ratio between aggregate and fine material is (60 to 70): (8 to 12).

[0088] The preparation method of the high-strength alkali-resistant and anti-scaling castable is specifically as described above.

[0089] Example 5

[0090] The high-strength alkali-resistant and anti-scaling castable comprises, by weight, 60 parts of low-aluminum mullite complex phase raw material particles, 12 parts of low-aluminum mullite complex phase raw material fine powder, 8 parts of silica fume, 7 parts of aluminate cement, 7 parts of alumina powder, 2 parts of metallic silicon powder, 4 parts of flake graphite, 0.1 parts of explosion-proof fiber, and 0.15 parts of sodium hexametaphosphate.

[0091] Wherein, the preparation method of the low-aluminum mullite multiphase raw material is as follows:

[0092] According to the weight proportion, 90 parts of low-grade fourth-grade raw alumina and 10 parts of potassium feldspar are weighed, crushed into particles below 20 mm, put into a ball mill, add water and wet grind for 10 to 20 hours, until the ball mill mud 325 mesh screening rate is ≥90%, use a plate and frame filter press to separate the mud and water, after the mud is trapped for 24 hours, use a vacuum extruder to extrude and shape, dry at 110 to 130 ℃ for 24 hours, sinter the dried sample at 1560 ℃ for 3 to 6 hours, and then crush it to obtain the product.

[0093] The prepared low-aluminum mullite composite raw material has an aluminum-silicon ratio A / S of 1.1, a Fe2O3 mass fraction of 1.49%, a R2O (K2O+Na2O) mass fraction of ≥2.0%, and a bulk density of 2.48 g / cm 3 The mullite content is 51.24%, and the high-silica glass phase content is 48.76% (the relative contents of mullite phase and high-silica glass phase are detected by hydrofluoric acid dissolution method (YB / T 4584-2017)).

[0094] The aluminum-silicon ratio A / S of the quaternary raw bauxite is 1.0-1.1, the mass fraction of Fe2O3 is ≤2.0%, and the mass fraction of R2O (K2O+Na2O) is ≤0.5%; the aluminum-silicon ratio A / S of the coal gangue is 0.8-0.9, the mass fraction of Fe2O3 is ≤1.5%, and the mass fraction of R2O (K2O+Na2O) is ≤0.5%; the aluminum-silicon ratio A / S of the potassium feldspar is 0.3-0.4, the mass fraction of Fe2O3 is ≤1.0%, and the mass fraction of R2O (K2O+Na2O) is ≥14.0%.

[0095] The low aluminum mullite complex phase raw material particles include low aluminum mullite complex phase raw material particles with a particle size of 0 to 8 mm, the low aluminum mullite complex phase raw material fine powder includes low aluminum mullite complex phase fine powder with a particle size of ≤200 mesh, the low aluminum mullite complex phase raw material particles are used as aggregate, the low aluminum mullite complex phase raw material fine powder is used as fine material, and the mass ratio between aggregate and fine material is (60 to 70): (8 to 12).

[0096] The preparation method of the high-strength alkali-resistant and anti-scaling castable is specifically as described above.

[0097] Comparative Example 1

[0098] The preparation formula of the anti-scaling high-strength castable includes, by weight, 60 parts of silicon carbide particles, 9 parts of alumina powder, 6 parts of silica fume, 7 parts of calcium aluminate cement, 0.1-0.2 parts of polypropylene explosion-proof fiber; 18 parts of magnesium aluminum spinel powder, and 0.2-0.3 parts of polycarboxylic acid water reducer. The preparation formula of Comparative Example 1 simulates the formula of the prior art and introduces silicon carbide and magnesium aluminum spinel. The preparation method is similar to that of Examples 1 to 5, as described above.

[0099] Table 1 Mechanical properties test results of Examples 1 to 5 and Comparative Example 1

[0100]

[0101]

[0102] By comparison, it is found that after firing at 1100°C, the flexural strength of Examples 1 to 5 is significantly improved compared with Comparative Example 1; after firing at 1400°C, the flexural strength of Examples 1 to 5 is basically maintained at the same level as that of Comparative Example 1. After firing at 1100°C and 1400°C, Examples 1 to 5 are significantly improved compared with Comparative Example 1. By comparison, we found that compared with the prior art comparative examples that introduced silicon carbide and aluminum magnesium spinel, Examples 1 to 5 have obvious advantages in flexural strength and compressive strength, and can withstand more extreme high-temperature use environments. Moreover, the raw materials used in Examples 1 to 5 are mainly raw alumina, coal gangue and potassium feldspar, which have lower material costs and better mechanical properties.

[0103] Figure 3 The pictures of the anti-scaling test results of Examples 1 to 5 and Comparative Example 1 are shown. It can be seen from the pictures that Comparative Example 1 produces a white reaction layer (scaling) on ​​the surface, which is the white circular area in the figure, and the circular area is the contact area of ​​the sample. The production of the white reaction layer indicates that oxidation has occurred, which is then easily corroded by alkali to cause the appearance of crusting, resulting in poor anti-scaling performance. In Examples 1 to 5, basically no white reaction layer is produced in the circular contact area, proving that there is no oxidation layer, it is not easy to be corroded by alkali, and the anti-scaling performance is good. Therefore, in summary, the present invention has achieved enhancement and improvement in strength, alkali resistance, and anti-scaling performance while making full use of low-cost raw bauxite and coal gangue.

[0104] The high-strength alkali-resistant and anti-scaling castable in the present invention is made of a low-aluminum mullite composite material as the main raw material, wherein the low-aluminum mullite composite raw material is prepared by mixing the ratio of quaternary raw alumina, coal gangue and potassium feldspar, and sintering at a high temperature of 1560°C to form a mullite-high silica glass phase composite material, and the relative content of the mullite phase and the high silica glass phase is detected by a hydrofluoric acid dissolution method (YB / T 4584-2017), and the phase composition ratio is adjusted so that the high silica glass phase is filled in the gap of the interwoven network structure formed by the needle-shaped or columnar mullite (see Figure 1 ), taking advantage of the high temperature viscosity of high silica glass phase, the pores in the castable are filled during service, a protective film is formed on the surface of the furnace lining, and the corrosion and penetration of alkali are prevented throughout the entire cycle, the anti-scaling and alkali resistance of the castable are improved, and the structure can also significantly improve the thermal shock resistance of the castable and reduce the expansion coefficient.

[0105] In the present invention, metal silicon powder and flake graphite are added to the components of the castable. The metal silicon powder melts at high temperature to block the pores on the surface of the castable, so that a reducing atmosphere is formed inside. The metal silicon powder and flake graphite can generate silicon carbide whiskers in situ in the matrix under the high temperature reducing atmosphere (see Figure 2 ), on the one hand, the in-situ generation of silicon carbide promotes the improvement of anti-scaling performance, on the other hand, the existence of silicon carbide in the form of whiskers can improve the high-temperature thermal shock resistance of the castable, and at the same time, the high silica glass phase in the low-aluminum mullite composite raw material powder wraps the in-situ silicon carbide, which effectively alleviates its oxidation reaction and further ensures the anti-scaling ability of the service life.

[0106] The invention relates to the field of refractory materials, in particular to a high-strength alkali-resistant low-aluminum mullite anti-scaling castable and a preparation method thereof. The castable uses a series of low-aluminum mullite composite raw materials prepared from low-grade bauxite, coal gangue and potassium feldspar as main aggregates, and comprises 60-70 parts of low-aluminum mullite composite raw material particles, 8-12 parts of low-aluminum mullite composite raw material fine powder, 6-8 parts of silica fume, 7 parts of aluminate cement, 4-6 parts of alumina micropowder, 1-2 parts of metallic silicon powder, 2-4 parts of flake graphite, 0.1 part of explosion-proof fiber and 0.1-0.15 part of water reducing agent, wherein the low-aluminum mullite composite material is a network structure in which a high silica glass phase is wrapped and filled in needle-shaped or columnar mullite interwoven with each other, and the mullite phase accounts for 44-52% of the phase content. The present invention not only improves the resource utilization rate and added value of bulk aluminum silicon solid wastes such as low-grade bauxite and coal gangue, but also overcomes the problems of high formula cost, oxidation failure during use, and poor anti-scaling effect of castables caused by attenuation of thermal shock resistance in the existing technology by adding additional silicon carbide and magnesium aluminum spinel to improve anti-scaling performance. The high-strength alkali-resistant anti-scaling castable prepared by the present invention has low linear expansion coefficient, high strength at high temperature, and excellent thermal shock resistance, alkali resistance and anti-scaling performance, and is suitable for key parts such as cement kiln tail smoke chamber, decomposition furnace, preheater, etc.

[0107] The present invention has been described by the above-mentioned relevant embodiments, however, the above-mentioned embodiments are only examples for implementing the present invention. It must be pointed out that the disclosed embodiments do not limit the scope of the present invention. On the contrary, changes and modifications made without departing from the spirit and scope of the present invention are all within the scope of patent protection of the present invention.

Claims

1. A high-strength alkali-resistant and anti-scaling castable, characterized in that: According to the weight percentage, it contains 60-70 parts of low-aluminum mullite composite raw material particles, 8-12 parts of low-aluminum mullite composite raw material fine powder, 6-8 parts of silica fume, 7 parts of aluminate cement, 4-6 parts of alumina powder, 1-2 parts of metallic silicon powder, 2-4 parts of flake graphite, 0.1 parts of explosion-proof fiber, and 0.1-0.15 parts of water reducing agent; The weight proportions of the low-aluminum mullite multiphase raw material particles, the low-aluminum mullite multiphase raw material fine powder, the silica fume, the aluminate cement, the alumina powder, the metallic silicon powder and the flake graphite are 100 parts in total, and the explosion-proof fiber and the water reducing agent are added additionally.

2. The high-strength alkali-resistant and anti-scaling castable according to claim 1, characterized in that: The low-aluminum mullite multiphase raw material used in the low-aluminum mullite multiphase raw material particles and the low-aluminum mullite multiphase raw material fine powder is prepared by the following preparation method: According to the weight percentage, 10 to 90 parts of grade 4 raw bauxite, 0 to 80 parts of coal gangue, and 10 parts of potassium feldspar are weighed, crushed into particles below 20 mm, loaded into a ball mill, and wet-milled for 10 to 20 hours, until the ball mill mud 325 mesh screening rate is ≥90%, and the mud and water are separated by a plate and frame filter press. After the mud is trapped for 24 hours, it is extruded into a shape using a vacuum extruder, dried at 110 to 130°C for 24 hours, and the dried sample is fired at a high temperature of 1560°C for 3 to 6 hours and then crushed to obtain the product; Among them, the aluminum-silicon ratio A / S of the quaternary raw bauxite is 1.0-1.1, the mass fraction of Fe2O3 is ≤2.0%, and the mass fraction of R2O (K2O+Na2O) is ≤0.5%; the aluminum-silicon ratio A / S of the coal gangue is 0.8-0.9, the mass fraction of Fe2O3 is ≤1.5%, and the mass fraction of R2O (K2O+Na2O) is ≤0.5%; the aluminum-silicon ratio A / S of the potassium feldspar is 0.3-0.4, the mass fraction of Fe2O3 is ≤1.0%, and the mass fraction of R2O (K2O+Na2O) is ≥14.0%.

3. The high-strength alkali-resistant and anti-scaling castable according to claim 1, characterized in that: The low-aluminum mullite composite raw material has an aluminum-silicon ratio A / S of 0.8-1.1, a Fe2O3 mass fraction of ≤1.8%, a R2O (K2O+Na2O) mass fraction of ≥2.0%, and a bulk density of 2.2-2.5 g / cm 3 The mullite content is 44-52%, and the high silica glass phase content is 48-56%.

4. The high-strength alkali-resistant and anti-scaling castable according to claim 1, characterized in that: The low aluminum mullite complex phase raw material particles include low aluminum mullite complex phase raw material particles with a particle size of 0 to 8 mm, the low aluminum mullite complex phase raw material fine powder includes low aluminum mullite complex phase fine powder with a particle size of ≤200 mesh, the low aluminum mullite complex phase raw material particles are used as aggregate, the low aluminum mullite complex phase raw material fine powder is used as fine material, and the mass ratio between aggregate and fine material is (60 to 70): (8 to 12).

5. The high-strength alkali-resistant and anti-scaling castable according to claim 1, characterized in that: In the silica ash, the mass percentage of SiO2 is ≥95%, the mass percentage of Fe2O3 is ≤2.0%, and the ignition loss is ≤3.0%.

6. The high-strength alkali-resistant and anti-scaling castable according to claim 1, characterized in that: The aluminate cement is pure calcium aluminate cement, in which the mass percentage of Al2O3 is ≥68% and the 325 mesh screening rate is ≥80%.

7. The high-strength alkali-resistant and anti-scaling castable according to claim 1, characterized in that: The mass percentage of Al2O3 in the alumina micropowder is ≥99%, and the D50 particle size is ≤3μm.

8. The high-strength alkali-resistant and anti-scaling castable according to claim 1, characterized in that: The mass percentage of Si in the metal silicon powder is ≥98.5%, and the D50 particle size is ≤0.074 mm.

9. The high-strength alkali-resistant and anti-scaling castable according to claim 1, characterized in that: The mass percentage of C in the flake graphite is ≥96.0%, and the D50 particle size is ≤0.074 mm.

10. A method for preparing a high-strength alkali-resistant and anti-scaling castable, characterized in that: The following steps are involved: a. Firstly, various raw materials are weighed according to the high-strength alkali-resistant and anti-scaling castable material described in any one of claims 1 to 9; b. Put the weighed raw materials into a stirring pot for pre-mixing for 30 seconds, then add water at a uniform speed for stirring for 180 seconds. The amount of water added is 6.5% of the total weight of the raw materials. After stirring evenly, a mixed slurry is obtained; c. The obtained mixed slurry is poured into a triple mold for self-flowing molding, and then naturally hardened for 12 hours. After hardening, the slurry is demoulded and placed in a curing box for curing for 24 hours. d. Place the cured sample in an oven for drying at a temperature of 110°C for 24 hours; e. Place the dried sample into a high-temperature electric furnace for firing at 1100°C or 1400°C for 3 hours. After firing, cool to room temperature and the preparation is complete.

Citation Information

Patent Citations

  • A high-strength castable with anti-scabbing properties

    CN115650749B